Valorization of Click-Based Microporous Organic Polymer: Generation of Mesoionic Carbene-Rh Species for the Stereoselective Synthesis of Poly(arylacetylene)s - Cho, Kyoungil; Yang, Hee Seong; Lee, In Hwan; Lee, Sang Moon; Kim, Hae Jin; Son, Seung Uk (Journal of the American Chemical Society, 2021)
This work reports the functionalization of azide-Alkyne click-based microporous organic polymer (CMOP). The generation of triazolium salts and successive deprotonation induced mesoionic carbene species in hollow CMOP (H-CMOP). Rh(I) species could be coordinated to the mesoionic carbene species to form H-CMOP-Rh, showing excellent heterogeneous catalytic performance in the stereoselective polymerization of arylacetylenes.
Keywords: Arylacetylenes; Catalytic performance; Functionalizations; Mesoionic carbene; Microporous organic polymers; Stereoselective polymerization; Stereoselective synthesis